Discharge health education needs and experiences of patients with skeletal-related events from bone metastases: A qualitative study - Jing Shan; Shuangyan Wang; Fan Ding; Junli Liang; Jianxin Wang; Donglai Wang (PLoS ONE, 2026)
Objective To describe the health education needs and experiences of patients with skeletal-related events due to bone metastasis from solid tumours upon discharge and to provide a reference for the formulation of discharge health education plans for this population. Methods A qualitative descriptive design and purposive sampling method were used to select patients with skeletal-related events due to bone metastasis from solid tumours who were hospitalized in the orthopaedic department of a Class III Grade A cancer hospital in Hebei Province from June to July 2024 for in-depth semistructured interviews. A Colaizzi 7-step analysis method was used to refine the themes of the patients’ needs. Results The needs of solid tumour bone metastasis patients with skeletal-related events for discharge health education provided by medical staff were refined into five themes: 1) bone health knowledge needs: patients were eager to obtain in-depth knowledge beyond the definition of the disease, such as the specific warning of pathological fracture and the early identification of bone metastasis progression; 2) bone health self-management needs: the focus was on specific operation guidance, including the home application of analgesic stepwise therapy and the protection skills for bone destruction sites; 3) coping with daily life needs: patients were concerned about how to safely go to the toilet, take a bath and other daily activities under the risk of disability; 4) coping with psychological pressure needs: manifested as the counselling needs for fear of disability and psychological support to combat the “burden feeling” during long-term pain; and 5) family and social support needs: patients need a collaborative nursing model that includes family participation, as well as a remote consultation channel for continuous access to professional medical care after discharge. Three themes were extracted from the information experience: 1) barriers to understanding medical terms: the professional words used by medical staff (such as “skeletal-related events” and “bone scan”) confused patients, leading to incorrect interpretation or neglect of health education; 2) passive acceptance: patients were unable to obtain targeted information, and the existing education is mostly one-way indoctrination, which fails to consider the differences in personalized care after bone metastasis of different primary cancers (such as lung cancer, breast cancer and prostate cancer); and 3) the large amount of information leads to poor satisfaction: the large amount of fragmented data provided before discharge leads to information overload and cognitive fatigue among patients, and the actual mastery rate and application satisfaction after discharge are low. Conclusions Patients with skeletal-related events due to bone metastasis from solid tumours face challenges such as a lack of bone health knowledge, psychological distress and a lack of self-management ability when discharged from the hospital. Medical staff should formulate a personalized discharge health education plan according to the needs of patients.